Religion, Medicine, and Global Health in Uganda: Reflecting Critically on an Afternoon at Mulago Hospital. (18th July 2017) - Bruner, Jason
Abstract : In this article, I use three scenes from an afternoon of ethnographic fieldwork at Mulago Hospital in Kampala, Uganda as the occasion to consider the various ways in which religion, medicine and global health are imagined, reified and dissolved as contemporary categories. I use historical and contemporary literature to illuminate how these interactions are contextualized products of broader historical processes. I conclude by arguing that research on global health needs to take "religion" seriously as a venue in which people create and enact modes of life that they find meaningful and life sustaining, particularly those creations and practices that are unable to be quantified in global health metrics and research.